Unique regulation of TiO2 nanoporous topography on macrophage polarization via MSC-derived exosomes. (17th February 2023) - Wang, Jinjin; Wang, Yazheng; Li, Yi; He, Yide; Song, Wen; Wang, Qintao; Zhang, Yumei; He, Chenyang
Abstract: The comprehensive recognition of communications between bone marrow mesenchymal stem cells (bm-MSCs) and macrophages in the peri-implant microenvironment is crucial for implantation prognosis. Our previous studies have clarified the indirect influence of Ti surface topography in the osteogenic differentiation of bm-MSCs through modulating macrophage polarization. However, cell communication is commutative and multi-directional. As the immune regulatory properties of MSCs have become increasingly prominent, whether bm-MSCs could also play an immunomodulatory role on macrophages under the influence of Ti surface topography is unclear. To further illuminate the communications between bm-MSCs and macrophages, the bm-MSCs inoculated on Ti with nanoporous topography were indirectly co-cultured with macrophages, and by blocking exosome secretion or extracting the purified exosomes to induce independently, we bidirectionally confirmed that under the influence of TiO2 nanoporous topography with 80–100 nm tube diameters, bm-MSCs can exert immunomodulatory effects through exosome-mediated paracrine actions and induce M1 polarization of macrophages, adversely affecting the osteogenic microenvironment around the implant. This finding provides a reference for the optimal design of the implant surface topography for inducing better bone regeneration. Graphical Abstract: